2004
DOI: 10.1016/s0002-9440(10)63306-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Ovarian Carcinoma

Abstract: Ovarian cancer remains the fifth leading cause of cancer death for women in the United States. In this study, the gene expression of 20 ovarian carcinomas, 17 ovarian carcinomas metastatic to the omentum, and 50 normal ovaries was determined by Gene Logic Inc. using Affymetrix GeneChip HU_95 arrays containing approximately 12,000 known genes. Differences in gene expression were quantified as fold changes in gene expression in ovarian carcinomas compared to normal ovaries and ovarian carcinoma metastases. Genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
165
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 66 publications
7
165
1
1
Order By: Relevance
“…27 Significant increase of claudin-4 has been detected in pancreatic, 22,28 prostate, 20 cervical 26 and ovarian cancers. 29 For the first time, our study detected high expression of claudin-4 in biliary tract cancers in contrast to hepatocellular carcinomas at both RNA and protein levels. This is in correlation with its expression in normal extrahepatic and intrahepatic bile ducts, gallbladder mucosa and its absence from hepatocytes shown by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 52%
“…27 Significant increase of claudin-4 has been detected in pancreatic, 22,28 prostate, 20 cervical 26 and ovarian cancers. 29 For the first time, our study detected high expression of claudin-4 in biliary tract cancers in contrast to hepatocellular carcinomas at both RNA and protein levels. This is in correlation with its expression in normal extrahepatic and intrahepatic bile ducts, gallbladder mucosa and its absence from hepatocytes shown by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have confirmed the overexpression of claudin-3 and claudin-4 in ovarian cancer [7][8][9][10][11][12][13][14], but the roles of these proteins in tumorigenesis or the mechanisms regulating them are unclear. As a first step in elucidating the role of claudin phosphorylation in ovarian cancer, we have recently shown that claudin-3 can be phosphorylated by PKA at Thr192, and that phosphorylation of this residue could lead to the disruption of TJs in ovarian cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, paradoxically, claudins have also been shown to be elevated in several cancers [5]. For example, we and others have shown that claudin-3 and claudin-4 are highly increased in ovarian cancer [7][8][9][10][11][12][13][14]. These claudins have also been shown to be elevated in prostate, pancreatic, uterine, and breast cancer [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that CLDN3 and CLDN4 are highly increased in ovarian cancer. [5][6][7][8][9][10][11][12] These claudins have also been shown to be elevated in prostate, pancreatic, uterine and breast cancer. [13][14][15] The functional roles for the overexpressed claudin proteins in human cancer are still unclear.…”
Section: Introductionmentioning
confidence: 99%